Performance determinants of fixed gear cycling during criteriums - Babault, N.; Poisson, M.; Cimadoro, G.; Cometti, C.; Païzis, C. (European Journal of Sport Science, 2018)
Nowadays, fixed gear competitions on outdoor circuits such as criteriums are regularly organized worldwide. To date, no study has investigated this alternative form of cycling. The purpose of the present study was to examine fixed gear performance indexes and to characterize physiological determinants of fixed gear cyclists. This study was carried out in two parts. Part 1 (n = 36) examined correlations between performance indexes obtained during a real fixed gear criterium (time trial, fastest laps, averaged lap time during races, fatigue indexes) and during a sprint track time trial. Part 2 (n = 9) examined correlations between the recorded performance indexes and some aerobic and anaerobic performance outputs (VO2max, maximal aerobic power, knee extensor and knee flexor maximal voluntary torque, vertical jump height and performance during a modified Wingate test). Results from Part 1 indicated significant correlations between fixed gear final performance (i.e. average lap time during the finals) and single lap time (time trial, fastest lap during races and sprint track time trial). In addition, results from Part 2 revealed significant correlations between fixed gear performance and aerobic indicators (VO2max and maximal aerobic power). However, no significant relationship was obtained between fixed gear cycling and anaerobic qualities such as strength. Similarly to traditional cycling disciplines, we concluded that fixed gear cycling is mainly limited by aerobic capacity, particularly criteriums final performance. However, specific skills including technical competency should be considered